Teacher competencies and digital integration into teaching practices: perceptions from pre-service biology teachers in Kazakhstan - Abiltayeva, Assem; Zhumagulova, Kalampyr; Satayev, Malik; Yechshzhanov, Talgat; Maimatayeva, Assiya; Balta, Nuri (Frontiers in Education, 2025)
This study investigates the self-reported teaching competencies, attitudes, and digital content usage of pre-service biology teachers in Kazakhstan. Competencies in this study refer specifically to the teachers' levels of pedagogical knowledge, content knowledge, and technological knowledge, as conceptualized by the Technological Pedagogical Content Knowledge (TPACK) framework. The research also examines how these self-reported competencies relate to demographic variables (gender, grade level, institutional affiliation, and stipend status) and institutional characteristics. Data were collected from 240 participants across three universities using two structured surveys. The findings indicate high self-reported competencies in TPACK domains, with significant variations in Technological Knowledge (TK) and digital content attitudes across gender, grade levels, and institutions. Female participants rated their competencies higher in multiple domains, while students in their final year of study exhibited greater scores in TPACK. Institutional differences were significant for the three different institutions. Stipend status was associated with minimal differences in most competencies, except for TK, where stipend recipients scored higher. Despite positive attitudes toward digital content, participants reported lower frequency of use and technological proficiency, indicating a gap between attitudes and practical application. Correlational analyses indicated that self-reported professional knowledge is closely linked to their digital content usage patterns and attitudes, stressing the interconnected nature of knowledge, behavior, and beliefs in the context of digital integration in education. These findings point out the need for targeted interventions, equitable resource allocation, and hands-on training in teacher preparation programs.